Սպանություն կատարած անձանց տագնապայնության և ագրեսիվության ուսումնասիրումը - Հովակիմյան, Հ. Ռ. (Մանկավարժ հրատ․)
Հոդվածում քննարկվում է սպանություն կատարած դատապարտյալների հոգեվիճակին վերաբերող վերասոցիալականացմանն ուղղված երկու խմբերի՝ վերասոցիալականացման ծրագրերին մասնակցած և չմասնակցած համեմատական վերլուծություններ` ըստ տագնապայնության և ագրեսիվության ցուցանիշների, որոնց արդյունքում պարզվեց, որ վերասոցիալականացման ծրագրերին մասնակցած խումբն ունի ագրեսիվության և տագնապայնության ցածր ցուցանիշ: The article discusses a comparative analysis of two groups - participants and non-participants in the re-socialization programs, aimed at re-evaluating the mental state of convicts who committed murder according to the indicators of anxiety and aggressiveness, and as a result the group that participated in the re-socialization programs turned out to have a low indicator of aggressiveness and anxiety. The concept of re-socialization in psychology was first used by social psychologists A. Kennedy and I.D. Kerber - that is the secondary entry of a person with a social disadvantage into the socio-cultural environment. To N. Smelzer's approach, re-socialization is the mastering of new values, roles, as well as new skills instead of previously insufficiently studied outdated skills. The perpetrators of the murder are serving long-term imprisonment. Criminal punishments, being important and effective means of combating crime, generate negative consequences of a social and socio-psychological nature. В статье, относящейся к ресоциализации, проводится сравнительный анализ психического состояния осуждѐнных за совершѐнные ими убийства. Данный анализ направлен на сравнение двух групп – участвующих и неучаствующих в программе ресоциализации в соответствии с показателями внутренней тревоги и агрессивности. В результате было выявлено, что группа, участвующая в программе ресоциализации, обладает показателем низкой агрессивности и внутренней тревоги.
Keywords: Հոգեբանություն